PENERAPAN HUKUM TERHADAP HARTA SITA MARITAL DALAM PERKARA PEMBAGIAN HARTA BERSAMA DALAM PERCERAIAN SUAMI ISTRI MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Indah Veramita Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThe results showed that the Plaintiffs filed suit based on marital seizure because of concerns about the abuse of joint property in divorce. Plaintiff does not combine with a lawsuit for divorce marital property / joint property in accordance with applicable laws in Indonesia based on the jurisprudence of the Supreme Court of the Republic of Indonesia Number 913 / K / Sip / 1982 dated May 21, 1983. While the reality is often the case, a lawsuit Divorce takes a very long time, starting from the first to the appeal.Lawsuit new division of joint property can be submitted after the divorce ruling permanent legal power. According to the UUP in the event of divorce between husband and wife has not become effective. Doubts in determining the applicable law in the field of joint property would have caused difficulties in its completion. Where the sub 4 said that about the marital property was not regulated in the PP 9 In 1975 therefore can not be treated effectively and naturally for the things that are still treated the provisions of law and the old law. Keywords : divorce, property